THE ONTOLOGICAL EINSTEIN – FOUR CASES IN POINT - Otto E. Rossler; Dieter Frohlich (European Scientific Journal, ESJ, 2013)
The four points which are the message of this paper are as follows: (i) ontological clock slow-down, downstairs in gravity; (ii) ontological rest-mass decrease, downstairs in gravity; (iii) ontological size increase, downstairs in gravity; and (iv) ontological charge decrease, downstairs in gravity. The simplest proofs of these partially unfamiliar results are sketched and their far-reaching consequences pointed at.